2015
DOI: 10.12659/pjr.895178
|View full text |Cite
|
Sign up to set email alerts
|

PH Measurements of the Brain Using Phosphorus Magnetic Resonance Spectroscopy (31PMRS) in Healthy Men – Comparison of Two Analysis Methods

Abstract: SummaryBackgroundIntracellular pH provides information on homeostatic mechanisms in neurons and glial cells. The aim of this study was to define pH of the brain of male volunteers using phosphorus magnetic resonance spectroscopy (31PMRS) and to compare two methods of calculating this value.Material/MethodsIn this study, 35 healthy, young, male volunteers (mean age: 25 years) were examined by 31PMRS in 1.5 T MR system (Signa Excite, GE). The FID CSI (Free Induction Decay Chemical Shift Imaging) sequence was use… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 44 publications
(22 citation statements)
references
References 33 publications
(61 reference statements)
0
22
0
Order By: Relevance
“…However, MG were not considered in these publications of our group, this being the first contribution in the literature dedicated to MG [12,13]. At the same time that these conceptual changes in oncology were taking place, the interest raised by the abnormalities of the intracellular and the extracellular pH (pHi and pHe) of both normal and brain cancer cells have shown a most beneficial “side effect” in the understanding the many levels of the pH-related paradigm, and/or the hydrogen ion (H + ) dynamics of cancer [3,13,14,15,16,17,18,19,20,21].…”
Section: Towards a New Perspective And Clinical Approach To Malignmentioning
confidence: 99%
“…However, MG were not considered in these publications of our group, this being the first contribution in the literature dedicated to MG [12,13]. At the same time that these conceptual changes in oncology were taking place, the interest raised by the abnormalities of the intracellular and the extracellular pH (pHi and pHe) of both normal and brain cancer cells have shown a most beneficial “side effect” in the understanding the many levels of the pH-related paradigm, and/or the hydrogen ion (H + ) dynamics of cancer [3,13,14,15,16,17,18,19,20,21].…”
Section: Towards a New Perspective And Clinical Approach To Malignmentioning
confidence: 99%
“…Additionally, differences between the pH values calculated in the present study and those reported by other research teams could result from the varied locations of the examined areas, because the pH values in various regions of the brain are different . The method of calculating pH is also significant . Therefore, in the Discussion, we do not quote any specific pH values reported by any researchers, and only make reference to age‐related pH changes observed by them.…”
Section: Discussionmentioning
confidence: 56%
“…If necessary, the phase was manually corrected (zero‐order phase correction, first‐order phase correction) and the entire spectrum was shifted along the x ‐axis so that the peak corresponding to the concentration of phosphocreatine (PCr) was at a value of 0 ppm. The pH value was calculated using the Henderson–Hasselbalch formula: italicpH=6.66+italiclogitalicδpi3.085.57italicδpi where: δpi – difference between chemical shift of inorganic phosphate (P i ) and PCr.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, brain pH can be measured using 31 P‐MRS by calculating the chemical shift difference between PCr and Pi (Cichocka et al., 2015; Petroff & Prichard, 1983). Normal brain activity can be associated with task‐related pH changes, as can environmental factors such as altitude (Shi et al., 2014).…”
Section: Introductionmentioning
confidence: 99%